Kajian Potensi Pengembangan Industri Gula Kelapa Untuk Mendorong Implementasi SDGs Di Desa Durensari - Defi Pinasti (STIE Rajawali Purworejo, 2024)
This research aims to determine the potential for developing the coconut sugar industry to encourage the implementation of the SDGs and determine the factors that support and hinder the development of the coconut sugar industry in Durenombo II Hamlet, Durensari Village. This research uses descriptive qualitative methods. Data was collected by interviews, documentation, literature study and observation. The research results show that (1) The potential for developing the coconut sugar industry in Durenombo II Hamlet, Durensari Village, has succeeded in encouraging the implementation of village SDGs, including: Villages without poverty, Villages without hunger, Healthy and prosperous villages, Quality village education, Villages worthy of clean water and sanitation, and Partnership for village development. (2) Supporting factors, namely, the existence of the Business Partner Cooperative helps craftsmen in marketing coconut sugar, provides capital, and improves the organizational and management capabilities of the community. Furthermore, the inhibiting factors are limited raw materials, limited labor, and limited equipment for producing coconut sugar.